PITUTUR: SEBUAH KOMPOSISI KARAWITAN DALAM PERSPEKTIF REPRESENTASI KENAKALAN REMAJA - Bambang Sri Atmojo; Aji Santoso Nugroho (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This Pitutur composition is a composition of songs worked on lirihan. In the Pitutur composition, the embodiment of the idea or idea of song composition is presented by containing a special ensemble consisting of 4 instruments, namely: Slenthem, Gender barung, gender penerus and ketuk kenong laras pelog patet nem. In this composition there is no kendang instrument, with the premise that in the presentation of his work it is expected that the players will be more sensitive to the ulat-ulatan system and adumanising rasa. As for the vocals of the Pitutur composition, it is more dominated by choral vocals (together). The creation of poetry is based on observing the reality of juvenile delinquency that has hit small towns in Indonesia, such as gangs, graffiti, theft, hold-ups, drunkenness and murder.The research method in creating a speech composition is through two stages, namely the preparation stage and the implementation stage. The results of the work show that the composition works on several gender beats which can give a new flavor, including garap buka which is sung by gender barung and the successor simultaneously so that it creates a dynamic atmosphere, working on the imbal-imbalan is presented at a slow tempo creating a sareh (calm) atmosphere, while at a slow tempo quickly creates an atmosphere of greget (firm), works on kinthilan creates an atmosphere of sigrak (enthusiasm), works on joy, creates an atmosphere of prenes (happy). Kata kunci: Pitutur; ensembel gender; komposisi; lirihan, vokal koor